2019
DOI: 10.3390/antiox8120578
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein, a Bioactive Compound from Olea europaea L., as a Potential Preventive and Therapeutic Agent in Non-Communicable Diseases

Abstract: Growing scientific literature data suggest that the intake of natural bioactive compounds plays a critical role in preventing or reducing the occurrence of human chronic non-communicable diseases (NCDs). Oleuropein, the main phenolic component of Olea europaea L., has attracted scientific attention for its several health beneficial properties such as antioxidant, anti-inflammatory, cardio- and neuro-protective, and anti-cancer. This article is a narrative review focused on the current literature concerning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 180 publications
2
99
0
Order By: Relevance
“…Thus, the inhibition of glycolysis by OLEO acquires a great significance for the targeting of cancer cell growth and expansion. Our findings, together with previous evidence showing the anti-cancer effects exerted by OLEO, pure Ole and analogs [23,53,54], reinforce the hypothesis to propose the use of these natural compounds in combination with conventional therapy used in the treatment of cancer.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, the inhibition of glycolysis by OLEO acquires a great significance for the targeting of cancer cell growth and expansion. Our findings, together with previous evidence showing the anti-cancer effects exerted by OLEO, pure Ole and analogs [23,53,54], reinforce the hypothesis to propose the use of these natural compounds in combination with conventional therapy used in the treatment of cancer.…”
Section: Resultssupporting
confidence: 86%
“…As to its anti-cancer properties, Ole affects and modulates multiple different biochemical processes and pathways involved in carcinogenesis. Indeed, Ole exerts an inhibitory effect on cancer cell proliferation, tumor growth and angiogenesis; it reduces inflammation and induces apoptosis [23][24][25]. In our previous study we found that Ole affects both the proliferation and the viability of A375 BRAF melanoma cells and potentiates their therapy response through pAKT/mTOR pathway [26].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As recently reported by the World Health Organization (WHO), Non-Communicable Diseases (NCDs) has been rising over the last century representing the main cause of death and disability for the general population regardless of age, region, or gender [1,2]. NCDs are chronic diseases characterized by long duration and slow progression that account for most ageing-related diseases including cardiovascular and neurodegenerative diseases, cancer, diabetes mellitus and chronic kidney disease.…”
mentioning
confidence: 99%
“…Among which olive oil, and in particular extra virgin olive oil (EVOO), is well recognized as one of the healthiest foods in the human diet [11]. The beneficial effects of EVOO is the result of the combination of functional components, such as fatty acid composition (with a high content of oleic acid) and wide minor bioactive constituents, among which polyphenols such as oleuropein from Olea europaea L. Several biological properties attributed to oleuropein, providing beneficial effects in the prevention of degenerative diseases, are mainly based on its antioxidant potential [12], but a recent review by Nediani et al [2] describes how oleuropein has multi-target activity including the anti-inflammatory [13], the anti-amyloid aggregation [14], anti-hypertensive [15], hypoglycemic [16], cardioprotective [17], autophagy inducer [18,19] and anticancer [20], also in combination with standard anti-cancer drugs [21]. In this context, the anti-proliferative and pro-apoptosis activity of oleuropein, in addition to its ability to reduce the glycolytic metabolism of different tumor types [22], it might represent an effective tool for complementary cancer therapy.…”
mentioning
confidence: 99%